EFEK SEDUHAN BUBUK KAYU MANIS TERHADAP GLUKOSA DARAH PENDERITA DIABETES MALLITUS TIPE 2 - Vonikartika, Arie; M. Hutapea, Albert (Ensiklopedia of Journal, 2024)
Diabetes is a silent killer that can kill, kill. Diabetes mellitus (DM) is caused by impaired pancreatic function, where the pancreas does not produce enough insulin or cannot use insulin effectively. DM is often characterized by chronic hyperglycemia. Diabetes Mellitus (DM) is a non-communicable disease (NCD) which is a public health problem, and has a fairly high number of sufferers in the world. There are many ways to treat and prevent DM, including changing a healthier lifestyle and using herbal treatment which can improve hyperglycemia in DM patients, one of which is cinnamon. Objective: to determine the effect of administering cinnamon powder on blood glucose in diabetes mellitus sufferers. Method: literature review design, journal data sources were obtained through a search using the database: Crom, Goggle scholer, journals published in 2019-2023. The journal data list in this study was created based on title, full title, full text and methodology assessed for study feasibility. Data tabulation and narrative analysis and study findings were conducted. Results and analysis: based on a journal that discusses the effect of cinnamon powder on reducing blood glucose in T2DM sufferers. Conclusion: giving cinnamon powder to diabetes mellitus sufferers can reduce blood sugar levels. This is because polyphenols help insulin to enter blood sugar into cells that accumulate in blood vessels so that the body's metabolic processes are fulfilled. Keywords: Diabetes Mellitus, Cinnamon Powder, Blood glucose, Effect, literature review.